Heavy metals found in the breathing zone,toenails and lung function of welders working in an air-conditioned welding workplace - Hariri, Azian; Mohamad Noor, Noraishah; Paimana, Nuur Azreen; Ahmad Zaidi, Ahmad Mujahid; Zainal Bakri, Siti Farhana (Taylor & Francis, 2017)
Welding operations are rarely conducted in an air-conditioned room. However, a company would set its welding operations in an air-conditioned room to maintain the humidity level needed to reduce hydrogen cracks in the specimen being welded. This study intended to assess the exposure to metal elements in the welders’ breathing zone and toenail samples. Heavy metal concentration was analysed using inductively coupled plasma mass spectrometry. The lung function test was also conducted and analysed using statistical approaches. Chromium and manganese concentrations in the breathing zone exceeded the permissible exposure limit stipulated by Malaysian regulations. A similar trend was obtained in the concentration of heavy metals in the breathing zone air sampling and in the welders’ toenails. Although there was no statistically significant decrease in the lung function of welders, it is suggested that exposure control through engineering and administrative approaches should be considered for workplace safety and health improvement.